Assessment of functional capacity of elderly patients hospitalized in the departments of lung diseases - Wysokiński, Mariusz; Lenartowicz, Halina; Fidecki, Wiesław; Przylepa, Katarzyna; Jędrzejewska, Aneta (Journal of Education, Health and Sport, 2018)
Introduction: Changes in the body related to the aging process and occurring diseases can significantly impede independent functioning in everyday life. Functional fitness of an elderly person can be seen as the ability to perform everyday, normal activities independently and with no effort. The aim of the study: The aim of the study was to determine the functional efficiency of elderly patients hospitalized in the department of lung disease Material and methods: The research was carried out in the lung diseases department of the Clinical Hospital No. 4 in Lublin. The group consisted of 153 patients aged from 65 to 89 years. 53.60% of the respondents were women. The research material was collected using the NOSGER scale (Nurses’ Observation Scale for Geriatric Patients). Results: In the assessment of patients, the result for the whole group was obtained at the average level of 73.91+11.42 points. The respondents functioned the worst in the area of instrumental activities of everyday life (13.53 points) and in the field of social behavior (13.54 points). The respondents functioned in the best way in the field of memory (8.01 points). Younger respondents (65-70 years old) performed better at 71.05+1.12 points. Women had higher functional fitness (72.03+11.23 points). The best biopsychosocial efficiency was demonstrated by people with higher education 68.91+9.00 points. Patients from the urban environment performed better compared to people from rural areas (79.32±10.12 points vs. 82.20±11.00 points). Conclusions: Elderly patients hospitalized in the department of lung diseases were characterized by reduced biopsychosocial efficiency. The largest deficits occurred in the field of instrumental activities of everyday life and social behavior. Age, gender, education and place of residence significantly differentiated the degree of functional efficiency of the examined patients.